2010
DOI: 10.1515/ijamh.2010.22.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding psychosocial competence for unmarried adolescent pregnancies using an integrated intervention

Abstract: This study was designed to investigate effects of an integrated intervention on psychosocial competence after abortion in unmarried adolescent pregnancies. Study Group: Three hundred eighty-five unmarried adolescent pregnancies aged 15 to 24 years (75.1% employed, 24.9% students) were recruited in the study, of which 190 were allocated into the experimental group and the rests as controls. Methods: The Rosenberg Self-esteem Scale (SES), the shortened version of Tyler's Behavioral Attributes of Psychosocial Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Two studies used prospective cohort designs (Roberts et al, 2017;Veiga et al, 2011). Half of the trials recruited women undergoing surgical abortion (Chor et al, 2015;Guerrero et al, 2012;Veiga et al, 2011;Wilson et al, 2017;Wu et al, 2012), while other trials either included women having a medical abortion (Constant et al, 2014;Gerdts et al, 2020) or did not limit inclusion on type of abortion (Roberts et al, 2017;Sonalkar et al, 2017;Yu et al, 2010). Most studies presented adequate information regarding the research background, participants' eligibility criteria, randomization, baseline data, and statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies used prospective cohort designs (Roberts et al, 2017;Veiga et al, 2011). Half of the trials recruited women undergoing surgical abortion (Chor et al, 2015;Guerrero et al, 2012;Veiga et al, 2011;Wilson et al, 2017;Wu et al, 2012), while other trials either included women having a medical abortion (Constant et al, 2014;Gerdts et al, 2020) or did not limit inclusion on type of abortion (Roberts et al, 2017;Sonalkar et al, 2017;Yu et al, 2010). Most studies presented adequate information regarding the research background, participants' eligibility criteria, randomization, baseline data, and statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…And among eight included RCTs, only four (Chor et al, 2015; Constant et al, 2014; Gerdts et al, 2020; Guerrero et al, 2012) presented a power analysis to determine the adequate sample size for detecting a significant effect of interventions. Three RCTs (Gerdts et al, 2020; Guerrero et al, 2012; Yu et al, 2010) and one cohort study (Veiga et al, 2011) did not provide any information related to blinding or other attempts to limit bias. Moreover, only one trial (Guerrero et al, 2012) reported information on the unintended effects of the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations